Role of Tobramycin in the Induction and Maintenance of Viable but Non-Culturable Pseudomonas aeruginosa in an In Vitro Biofilm Model - Gianmarco Mangiaterra; Nicholas Cedraro; Salvatore Vaiasicca; Barbara Citterio; Roberta Galeazzi; Emiliano Laudadio; Giovanna Mobbili; Cristina Minnelli; Davide Bizzaro; Francesca Biavasco (MDPI AG, 2020)
The recurrence of Pseudomonas aeruginosa (PA) biofilm infections is a major issue in cystic fibrosis (CF) patients. A pivotal role is played by the presence of antibiotic-unresponsive persisters and/or viable but non-culturable (VBNC) forms, whose development might be favored by subinhibitory antibiotic concentrations. The involvement of tobramycin and ciprofloxacin, widely used to treat CF PA lung infections, in the abundance of VBNC cells was investigated in PA biofilms models. In vitro biofilms of the laboratory strain PAO1-N and the clinical strain C24 were developed and starved by subculture for 170 days in a non-nutrient (NN) broth, unsupplemented or supplemented with one-quarter minimal inhibitory concentration (MIC) of tobramycin or ciprofloxacin. VBNC cells abundance, estimated as the difference between total live (detected by qPCR and flow cytometry) and colony forming unit (CFU) counts, showed a strain- and drug-specific pattern. A greater and earlier abundance of VBNC PAO1-N cells was detected in all conditions. Exposure of the C24 strain to NN and NN + ciprofloxacin induced only a transient VBNC subpopulation, which was more abundant and stable until the end of the experiment in tobramycin-exposed biofilms. The same response to tobramycin was observed in the PAO1-N strain. These findings suggest that low tobramycin concentrations might contribute to PA infection recurrence by favoring the development of VBNC forms.